Efficacy of Vitamin C in Reducing Duration of Severe Pneumonia in Children - Imran Mahmood Khan ,Asma Shabbier ,Samiya Naeemullah ,Farah Rashid Siddiqui , Mahwish Rabia , Saba Naim Khan , Muhammad Tahir Chaudhary (Journal of Rawalpindi Medical College, 2014)
Background : To determine the efficacy of vitamin C in reducing duration of severe pneumonia in children Methods: In this descriptive study children suffering from pneumonia , under age 5 were enrolled.. In vitamin C group (n=111), patient received 200mg of vitamin C once daily and in other group 111 children received placebo drops which matched exactly in color and taste. Clinical progress of both groups was taken thrice daily in terms of oxygen saturation, respiratory rate and chest in drawing. Results: Among 222 children, majority (61.71%) were male and 85(38.28%) were female. Majority (58.55%) were infants, 29.72% were between 1-3 years and 11.71% were between 4-5 years(15.14+7.76 months). Oxygen saturation was improved in < 01 day (p=0.003) and respiratory rate was improved in < 04 days (p=0.03) in vitamin C group. No statistically significant difference was found in chest in drawing. Conclusion: Vitamin C is effective in reducing duration of severe pneumonia in children less than five years of age.